1989
DOI: 10.1111/j.1525-1470.1989.tb00910.x
|View full text |Cite
|
Sign up to set email alerts
|

Pemphigoid in Children

Abstract: Pemphigoid is an autoimmune blistering disease that is rare in childhood. A review of the English, German, and French literature published prior to 1989 revealed 31 cases of juvenile bullous pemphigoid and 12 of other forms (10 cases of juvenile cicatricial and 2 of juvenile localized bullous pemphigoid). Childhood pemphigoid, although less frequent, seems no different than its adult counterpart. While oral lesions are more common in the juvenile bullous form, there is no association with malignancy, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
6

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 57 publications
(70 reference statements)
0
22
0
6
Order By: Relevance
“…Some children respond to dapsone or sulfapyridine, but we did not use these agents in our patients (15,19). Oral er>'thromycin and niacinamide have also been reported to be helpful, but there is very limited experience with this treatment, and we did not attempt it.…”
Section: Bullous Pemphigoidmentioning
confidence: 62%
“…Some children respond to dapsone or sulfapyridine, but we did not use these agents in our patients (15,19). Oral er>'thromycin and niacinamide have also been reported to be helpful, but there is very limited experience with this treatment, and we did not attempt it.…”
Section: Bullous Pemphigoidmentioning
confidence: 62%
“…Our findings agree with these observations. It has been suggested that almost all juvenile BP patients show disseminated disease (27), and all our patients except the child with localized vulval BP developed generalized blistering. Localized vulval BP has been suggested to be a distinct variant of childhood BP which responds well to topical corticosteroids, as in this patient, and does not lead to scarring (28).…”
Section: Discussionmentioning
confidence: 48%
“…However, they differ in some aspects: mucous membrane involvement has been reported more frequently in children. Oranje 4 reported mucosal findings in almost 50% of the patients studied, while Nemeth et al 2 . found mucous membrane involvement in 13 out of 18 (72%) children.…”
Section: Discussionmentioning
confidence: 90%
“…It usually clears the lesions rapidly, preventing the formation of new ones, as observed in our patient. Addition of dapsone or sulfapyridine as adjunctive therapy to steroids may be useful 4 . Oral erythromycin alone has also been used with good responses 16 .…”
Section: Discussionmentioning
confidence: 99%